Effect of Pituitary Gland (PG) Doses on Artificial Propagation of Endangered Tarabaim, Macrognathus aculeatus (Bloch) (Progressive Agriculture, 2013)
Five hormone doses viz., 40, 60, 70, 85 and 90 mg of Pituitary gland (PG)/kg body endangered Tarabaim (Macrognathus aculeatus) were tested and they were designated as Treatments T1, T2, T3, T4 and T5, respectively. Significantly (p